Progression in yield and value addition of Indian bread wheat – An analysis - Mohan, D.; Tiwari, V.; Gupta, R.K. (The Indian Journal of Genetics and Plant Breeding, 2017)
National wheat programme of India was examined for progress made in yield and quality in ten different production environments. During the period 2000-16, productivity improved in three environments namely timelysown condition of north-western plains zone (NWPZ) and timely and late-sown wheats of central zone (CZ). Certain non-grain parameters like plant height, vegetative period and crop duration were the significant contributors in these environments. Improvement in grain quality was zonespecific but simultaneous increase in productivity and value addition was witnessed in the most important region of the country i.e., NWPZ. Chapati quality and physical grain quality improved in the Indo-Gangetic plains and peninsular zone (PZ). Amongst the baked products; quality of the cookies was improvised in the hills whereas progress in bread loaf volume was visible in NWPZ and PZ. In quality components, protein content was enhanced in PZ and gluten characteristics were improved in NWPZ. Except reduction in bread quality score, no major change occurred in grain quality of the new varieties developed for hot and dry climate of central India.